Training Primary Care Physicians to Employ Self-Efficacy-Enhancing Interviewing Techniques: Randomized Controlled Trial of a Standardized Patient Intervention - Jerant, Anthony (J Gen Intern Med, 2016)
BACKGROUND: Primary care providers (PCPs) have few tools for enhancing patient self-efficacy, a key mediator of myriad health-influencing behaviors. OBJECTIVE: To examine whether brief standardized patient instructor (SPI)-delivered training increases PCPs’ use of self-efficacy-enhancing interviewing techniques (SEE IT). DESIGN: Randomized controlled trial. PARTICIPANTS: Fifty-two family physicians and general internists from 12 primary care offices drawn from two health systems in Northern California. INTERVENTIONS: Experimental arm PCPs received training in the use of SEE IT training during three outpatient SPI visits scheduled over a 1-month period. Control arm PCPs received a single SPI visit, during which they viewed a diabetes treatment video. All intervention visits (experimental and control) were timed to last 20 min. SPIs portrayed patients struggling with self-care of depression and diabetes in the first 7 min, then delivered the appropriate intervention content during the remaining 13 min. MAIN MEASURES: The primary outcome was provider use of SEE IT (a count of ten behaviors), coded from three audio-recorded standardized patient visits at 1–3 months, again involving depression and diabetes self-care. Two five-point scales measured physician responses to training: Value (7 items: quality, helpfulness, understandability, relevance, feasibility, planned use, care impact), and Hassle (2 items: personal hassle, flow disruption). KEY RESULTS: Pre-intervention, study PCPs used a mean of 0.7 behaviors/visit, with no significant between-arm difference (P = 0.23). Post-intervention, experimental arm PCPs used more of the behaviors than controls (mean 2.7 vs. 1.0 per visit; adjusted difference 1.7, 95 % CI 1.1–2.2; P < 0.001). Experimental arm PCPs had higher training Value scores than controls (mean difference 1.05, 95 % CI 0.68–1.42; P < 0.001), and similarly low Hassle scores. CONCLUSIONS: Primary care physicians receiving brief SPI-delivered training increased their use of SEE IT and found the training to be of value. Whether patients visiting SEE IT-trained physicians experience improved health behaviors and outcomes warrants study. CLINICALTRIALS.GOV IDENTIFIER: NCT01618552 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-016-3644-z) contains supplementary material, which is available to authorized users.